LGBTQ Related Intervention in Indonesia: a Literature Review - Winardy, Gary Collins Brata; Septiana, Eva (UI Scholars Hub, 2023)
Sexuality remains a divisive but relevant topic in Indonesia, especially concerning sexual minorities, societal view on sexuality, and what role education should take regarding sexuality. The views on the education field in Indonesia are separated on two camps, with some scholars decrying LGBTQ as a problem, a phenomenon incompatible with the national, cultural, and religious values. Whereas at the same time, other schools of thought are pushing for the integration and tolerance toward sexual minority. This article aims to review the current practices on how Indonesia education system handle the topic of LGBTQ. This is done through reviewing research articles that conduct intervention, education, or training that address the issue of LGBTQ. A within-case analysis will be carried out to analyze the articles in the dataset, and examining them based on method, justification or perceived urgency, stance toward the issue of LGBTQ, subject of the intervention and training, and intervention or training goal.